Giant foreign body granuloma after endoscopic management of vesicoureteric reflux: a case report - Saket Davera; Anjan Dhua; Shipra Agarwal; Mohamed Sulaiman (SpringerOpen, 2022)
Abstract Background Deflux®, a dextranomer/hyaluronic acid copolymer, is extensively used as an endoscopic bulking agent for management of vesicoureteric reflux (VUR). The complications following Deflux® treatment as described in the literature are clinically insignificant transient obstruction and infections of the urinary tract. We report a rare case of a giant Deflux® granuloma presenting as an intraoperative surprise while undergoing open ureteric reimplantation for the failure of prior endoscopic management. Case presentation A 2.5-year-old boy with a primary VUR needed Anderson Hyne's pyeloplasty of the affected side for concomitant pelviureteric junction obstruction. During removal of the double "J "stent in the postoperative period, subureteric Deflux® was injected, hoping that a more invasive procedure could be avoided. At a later date, as VUR persisted, an open ureteric reimplantation, was performed. Intraoperatively, a large Deflux® granuloma was noted at the site of previously injected site. Conclusions Giant Deflux® granuloma is a rare complication of this modality of VUR management. A focussed radiological assessment in such pateints during follow-up is required, especially those planned for surgical intervention in the vesicoureteric region later.